Análisis de las condiciones de crecimiento conjunto del casco urbano y los centros poblados del Municipio de Sopo de acuerdo con sus necesidades y crecimiento poblacional a 2034. (2022)
The municipality of Sopo, in the department of Cundinamarca, is one of the municipalities with the greatest projection for the future at a territorial level and in terms of interconnectivity of the central savannah region with the capital city and the northeast of the country, not only because of its geographical and spatial location, but not because of the cultural and social importance that has been strengthened in recent years thanks to the fact that Bogotá has focused its gaze on moving various massive events to the north of the city; more specifically in the Briceño sector.